OpenStreetMap data in modelling the urban energy infrastructure: a first assessment and analysis. (December 2017) - Alhamwi, Alaa; Medjroubi, Wided; Vogt, Thomas; Agert, Carsten
Abstract: Energizing the future energy systems requires comprehensive understanding at the urban level. However, many uncertainties hinder such goals, leastwise the data and tools used in modeling urban energy systems (UES). Urban Energy Modeling including spatial parameters of urban forms and settlements can lead to more sustainable approaches in computational simulations. Moreover, scientific policy advice requires that models and data to be transparent and prepared in an unbiased manner. Hence, benchmarking the quality criteria of open source datasets like OpenStreetMap (OSM) data is needed. This contribution introduces UES modelling and its data requirements for different application sectors. Further, it extends and provides a first assessment of OSM data which is used in modeling energy systems in cities. This data was previously used in the context of a UES model developed by the authors. A main conclusion is that although many OSM features are missing and cannot be extracted from OSM, these datasets constitute a great source of open data which can contribute to a more sustainable and transparent modelling.